Nivalios gen. nov. (Hemiptera: Fulgoromorpha: Flatidae), first record of the tribe Nephesini from China - Zhang, Ya-Lin; Peng, Ling-Fei; Wang, Ying-Lun (Zootaxa, 2011)
This paper describes one new flatid genus, Nivalios gen. n., and one new species, N. punctatus sp. n., from southern China. The new genus is assigned to the tribe Nephesini. A key to genera of the tribe Nephesini from the Oriental Region is provided. Scanning electron micrographs of the antennal sensilla, cross-sections through the subapical rostral segment and wax glands on the tegmen of the new species are included.